Comparison of Polar® RS800G3™ heart rate monitor with Polar® S810i™ and electrocardiogram to obtain the series of RR intervals and analysis of heart rate variability at rest. (27th October 2014) - de Rezende Barbosa, Marianne Penachini da Costa; Silva, Natália Turri da; de Azevedo, Fábio Mícolis; Pastre, Carlos Marcelo; Vanderlei, Luiz Carlos Marques
Summary: The Polar ® RS800G3 ™ rate monitor was released in the market to replace the Polar ® S810i ™, and few studies have assessed that the RR series obtained by this equipment is reliable for analysis of heart rate variability (HRV). We compared HRV indexes among the devices Polar ® RS800G3 ™, Polar ® S810i ™ and eletrocardiogram (ECG) to know whether the series of Polar ® RS800G3 ™ are as reliable as those devices already validated. We analysed data from 30 healthy young adults, male, with an average age of 20·66 ± 1·40 years, which had captured the heart rate beat to beat in the three devices simultaneously with spontaneously breathing, first in the supine position and subsequently sit both for 30 min. The obtained series of RR intervals was used to calculate the indexes of HRV in the time domain (SDNN and RMSSD) and in the frequency domain (LF, HF and LF/HF). There were no significant differences in HRV indexes calculated from series obtained by the three devices, regardless of the position analysed, and a high correlation coefficient was observed. The results suggest that the Polar ® RS800G3 ™ is able to capture series of RR intervals for analysis of HRV indexes as reliable as those obtained by ECG and Polar ® S810i ™ .